Immobilization and stabilization of cephalosporin C acylase on aminated support by crosslinking with glutaraldehyde and further modifying with aminated macromolecules. (2nd February 2015) - He, Hua; Wei, Yanmei; Luo, Hui; Li, Xi; Wang, Xiaona; Liang, Chen; Chang, Yanhong; Yu, Huimin; Shen, Zhongyao
<x xml:space="preserve">Abstract</x> In this work, cephalosporin C acylase (CA), a heterodimeric enzyme of industrial potential in direct hydrolysis of cephalosporin C (CPC) to 7‐aminocephalosporanic acid (7‐ACA), was covalently immobilized on the aminated support LX1000‐HA (HA) with two different protocols. The stability of CA adsorbed onto the HA support followed by crosslinking with glutaraldehyde (HA–CA–glut) was better than that of the CA covalently immobilized on the glutaraldehyde preactivated HA support (HA–glut–CA). The thermostabilization factors (compared with the free enzyme) of these two immobilized enzymes were 11.2‐fold and 2.2‐fold, respectively. In order to improve the stability of HA–CA–glut, a novel strategy based on postimmobilization modifying with aminated molecules was developed to take advantage of the glutaraldehyde moieties left on the enzyme and support. The macromolecules, such as polyethyleneimine (PEI) and chitosan, had larger effects than small molecules on the thermal stability of the immobilized enzyme perhaps due to crosslinking of the enzymes and support with each other. The quaternary structure of the CA could be much stabilized by this novel approach including physical adsorption on aminated support, glutaraldehyde treatment, and macromolecule modification. The HA–CA–glut–PEI20000 (the HA–CA–glut postmodified with PEI Mw = 20, 000) had a thermostabilization factor of 20‐fold, and its substrate affinity (Km = 14.3 mM) was better than that of HA–CA–glut (Km = 33.4 mM). The half‐life of the immobilized enzymes HA–CA–glut–PEI20000 under the CPC‐catalyzing conditions could reach 28 cycles, a higher value than that of HA–CA–glut (21 cycles). © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:387–395, 2015